Large-Scale Promotion of Animal Dung-based Domestic Biogas Digesters through Public Private Partnership: A Successful Case of Nepal - Pokharel, Govind Raj; Chettri, Arjun Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Large-scale promotion of small scale decentralized renewable energy technologies to achieve a part of millennium development goal remained a great challenge until recently. However, a properly implementation of a public private partnership applied in biogas sector in Nepal has shown that scaling up of small scale renewable energy technologies is feasible if a multi-stakeholder sector development approach and favorable policy as well as modality is adopted. Nepal’s biogas program has been instrumental in helping to achieve some of the Millennium Development Goals (MDGs) by creating economic and social development opportunities in a sustainable way. Such model could also be widely replicated in any other renewable energy technologies and other continent of the world. DOI: http://dx.doi.org/10.3126/hn.v8i0.4908 Hydro Nepal: Journal of Water, Energy and Environment Issue No. 8, 2011 January Page: 29-33 Uploaded date: 17 June, 2011